Bali: Between Cultural and Marine Tourism - I Nyoman Darma Putra (Jurnal Kajian Bali (Journal of Bali Studies), 2014)
AbstractThis paper discusses the potential of marine tourism in Bali and its contribution toward the development of sustainable tourism. While marine and cultural tourism form two distinct categories, in Bali there are many cultural activities that take place on beaches, or coastal areas that become unique tourist attractions. Therefore, in this paper, I willalso introduce an expanded view of marine tourism that would include, for instance, the observation of processions and rituals on beaches. Exploring the interconnections between marine and cultural tourism may help us come upwith new strategies for the sustainability of tourism in Bali as a whole. In addition to aiming at sharing the experiences of Bali in managing and promoting its marine tourism potential, this paper also seeks feedback on better waysto manage marine tourism in order to achieve tourism sustainability for the island.